Impact of match-induced pressure on HRV of junior tennis players - Fuentes-García, J. P.; Crespo, M.; Martínez-Gallego, R.; Villafaina, S. (Physiology & Behavior, 2022)
The present study aimed to assess the impact of a tennis competition on the HRV of nationally ranked junior girls and boys tennis players. A total of 22 nationally ranked tennis players (8 girls and 14 boys), with a mean age of 14.18 (2.15) and experience in national tournaments of 4.23 (2.27) years, participated in this cross-sectional study. Boys had a mean age of 14.36 (1.86) years-old and girls had a mean age of 13.87 (2.69) years old. Participants were assessed the day before and 20 min before the competition match. Significantly reduction in time-domain variables such as the time between intervals R-R (RR-interval) (p-value = 0.001), the percentage of intervals >50 ms different from the previous interval (pNN50) (p-value = 0.020) and the square root of the mean of the squares of the successive differences of the interval RR (RMSSD) (p-value = 0.028) were found between baseline and pre-match assessments. Furthermore, the non-linear measure based on the dispersion, standard deviation, of points perpendicular to the axis of line-of-identity in the Poincaré plot (SD1) (p-value = 0.028) was also significantly reduced before the match when compared to the baseline. However, differences between girls and boys junior tennis players were not found in the pre-competitive heart rate variability (HRV) variables (p-value >0.05). HRV is a convenient, non-invasive measurement that can be easily performed with a watch at home and on the field in order to control and manage match-induced pressure.